Analysis of Election Monitor Participation In Governance By Bawaslu In The Implementation of Elections - Mega Arum, Nawang (Asian Journal of Social and Humanities, 2024)
The purpose of this is to implement the law while creating a participatory election climate for the public. In the previous elections, the role of monitors was mostly focused on the D-day of voting, then what is the pattern of monitoring participation in the 2024 elections? As a non-structural state institution, this intersects with the implementation of governance so that it is the main problem in this study, where analyzing the participation of election monitors in governance is important to provide feedback in the implementation of electoral democracy. This study uses a descriptive qualitative approach with a research focus on the participation of election monitors as a representation in governance which is applied as an effort to prevent violations and other vulnerability issues. The results of the analysis show that the participation of election monitors includes policy making in the form of regulations (planning), the implementation of participation in the form of monitoring, and the resulting evaluation in the form of recommendations. At the level of governance, participation can be identified from the pattern of collaboration that shows the legitimacy of each other, upholding diversity and inclusivity both from the involvement of institutions that have a concentration on inclusive election issues and ideas built in election monitoring. In the implementation, it shows the expertise of each in showing participation to the level of public orientation so that public control is one of the important elements in realizing participatory election monitoring.